2013
DOI: 10.3126/njms.v2i2.8965
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal disease and obesity in an Indian population

Abstract: Background: Associations between obesity and several chronic inflammatory diseases are emerging. Research from some parts of the world has also indicated that a relationship between periodontal disease and obesity is possible. The aim of the present study was to determine the association of obesity with periodontal disease in a semi urban Indian population. Methods: Body Mass Index (BMI) was determined for 323 patients visiting the department of Periodontics. Other demographic variables such as age, gender, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“… 11 In the current study, periodontitis was observed in 71.3%. This was similar to those reported in India, 12 14 Brazil, and Chile: 62.6% and 58.6% respectively (>5 mm LOA) 15 but higher than reported in Chinese (25.9%) 2 and Korean (24.8%) 1 population (shallow and deep periodontal pockets). The reason for higher prevalence could be that this study was conducted at specialised periodontics clinic where the chances of individuals having periodontitis is always higher than general dental clinic.…”
Section: Discussionsupporting
confidence: 90%
“… 11 In the current study, periodontitis was observed in 71.3%. This was similar to those reported in India, 12 14 Brazil, and Chile: 62.6% and 58.6% respectively (>5 mm LOA) 15 but higher than reported in Chinese (25.9%) 2 and Korean (24.8%) 1 population (shallow and deep periodontal pockets). The reason for higher prevalence could be that this study was conducted at specialised periodontics clinic where the chances of individuals having periodontitis is always higher than general dental clinic.…”
Section: Discussionsupporting
confidence: 90%
“…This can possibly be a consequence of the complexity of the relationship between obesity, periodontitis, and potential confounding factors, including smoking, diabetes, aging, and alcohol consumption behavior. This finding is strengthened by other studies,[ 20 - 24 ] suggesting no association between obesity and periodontitis in adults after adjusting for potential confounders. This result is contrary to other epidemiological studies[ 25 - 28 ] that reported a substantial relationship between obesity and periodontitis.…”
Section: Discussionsupporting
confidence: 66%
“…In our study also patients were given regular oral hygiene instruction and basic periodontal therapy. There was a considerable improvement seen in their oral and systemic health [16].…”
Section: Discussionmentioning
confidence: 97%